PENGARUH FREE CASH FLOW, PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN (STUDI PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017) - Ayu Yossita Candra Octaviana; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT            This study aims to determine the effect of free cash flow, Profitability, Liquidity and Leverage on Dividend Policy. This study uses Explanatory Research. The population in this study were all Food and Beverage companies listed on the Indonesia Stock Exchange for the period 2015-2017, and samples of 12 companies. Methods of collecting data through the documentation method. Analysis of the data used is multiple linear regression analysis. In this study the data analysis used was using SPSS version 20. The sampling technique in this study used a purposive sampling method using several criteria. Data testing techniques in this study include: normality test, classic assumption test and multiple linear regression analysis, and hypothesis testing.The results of this study indicate that: (1) free cash flow has no significant effect on Dividend Policy, (2) Profitability has a significant effect on Dividend Policy, (3) Liquidity has no significant effect on Dividend Policy, and (4) Leverage has a significant effect on Dividend Policy.Keywords: Free Cash Flow, Profitability, Liquidity, Leverage, and Dividend Policy.